Microscale nuclear magnetic resonance gradient chip. (1st January 2023) - Meissner, M V; While, P T; Mager, D; Korvink, J G
Abstract: We propose a design, micro fabrication process, and nuclear magnetic resonance (NMR) based evaluation, of a magnetic field gradient chip. The uni-axial linear z -gradient coil design was computed by a stream-function method, with the optimisation goal to exhibit minimum power dissipation. The gradient coils were implemented on two bi-planes, which were built-up with Cu electroplating in combination with photo definable dry-film laminates. In the presented fabrication process, the initial seed layer served as a self-aligning back-side mask to define the electroplating mould, and also to implement resistive temperature detectors. The coil design and the electroplating process were tailored to enhance the electroplated height to construct low-resistive coils. Thermographic imaging in combination with the integrated temperature sensors allowed for investigating the heat-up, in order to analyse the current rating of the coil dual stack. The gradient coil was assembled with a radio frequency micro coil in a flip-chip configuration. To demonstrate the field linearity, a micro-engineered phantom was fabricated and subjected to a one-dimensional NMR experiment.